2021
DOI: 10.1136/bmjopen-2021-050945
|View full text |Cite
|
Sign up to set email alerts
|

‘Stressed, uncomfortable, vulnerable, neglected’: a qualitative study of the psychological and social impact of the COVID-19 pandemic on UK frontline keyworkers

Abstract: ObjectivesNon-healthcare keyworkers face distinct occupational vulnerabilities that have received little consideration within broader debates about ‘essential’ work and psychological distress during the COVID-19 pandemic. The aim of this study was therefore to explore the impact of the pandemic on the working lives and mental health and well-being of non-healthcare keyworkers in the UK.DesignIn-depth, qualitative interviews, analysed using a reflexive thematic analysis.SettingTelephone or video call interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 44 publications
2
43
1
Order By: Relevance
“…24 , 25 It is possible that individuals living with children had decreasing levels of arts engagement throughout the pandemic due to burnout and difficulties in sustaining a balance between work, childcare, schooling, and other responsibilities. 20 , 21 While previous studies have shown that people living in remote areas are more likely to engage in the arts, 7 , 26 we found no associations between living area and longitudinal patterns of arts engagement. This suggests that changes over time might not vary by level of urbanicity.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…24 , 25 It is possible that individuals living with children had decreasing levels of arts engagement throughout the pandemic due to burnout and difficulties in sustaining a balance between work, childcare, schooling, and other responsibilities. 20 , 21 While previous studies have shown that people living in remote areas are more likely to engage in the arts, 7 , 26 we found no associations between living area and longitudinal patterns of arts engagement. This suggests that changes over time might not vary by level of urbanicity.…”
Section: Discussioncontrasting
confidence: 79%
“…This working age group may have faced challenges around childcare while working, reducing time available for leisure. 20,21 The association between household income and arts engagement may also have been altered by the pandemic. Prepandemic studies have generally demonstrated more arts engagement with increasing income.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experienced, postgraduate, male and female, qualitative health researchers conducted all interviews (AB, ARM, JD, RC, SE, TM, LB). All interviewers have previously carried out interviews about mental health and social life throughout the COVID-19 pandemic for other CSS research work 20–22. Interviews followed a semi-structured format (range: 17–65 min, average 38), with prompts used to focus on each participant’s own lived experience of the COVID-19 pandemic.…”
Section: Methodsmentioning
confidence: 99%
“…Research undertaken in various locations globally, including Australia, reveals that COVID-19 (and the unique socioeconomic impacts it has wrought) has adversely impacted the mental health and well-being of diverse cohorts of people 14–20. We used the story completion method with Australian participants coping with measures put in place to limit the spread of COVID-19 to gain insights regarding the impact of the pandemic on mental health and well-being.…”
Section: Introductionmentioning
confidence: 99%